Human Relationships with Domestic and Other Animals: One Health, One Welfare, One Biology - Ariel M Tarazona; Maria C Ceballos; Donald M Broom (Animals, 2019)
Excessive human population growth, uncontrolled use of natural resources, including deforestation, mining, wasteful systems, biodiversity reduction by agriculture, and damaging climate change affect the existence of all animals, including humans. This discussion is now urgent and people are rethinking their links with the animals we use for clothing, food, work, companionship, entertainment, and research. The concepts of one health, one welfare, and one biology are discussed as a background to driving global change. Nothing should be exploited without considering the ethics of the action and the consequences. This review concerns domesticated animals, including those used for human consumption of meat, eggs, and milk; horses kept for work; and dogs kept for company. Animal welfare includes health, emotional state, and comfort while moving and resting, and is affected by possibilities to show behavior and relationships with others of the same species or with humans. We show some examples of the relations between humans and domesticated animals in the environmental context, including zoonotic diseases, and consider the consequences and the new paradigms resulting from current awareness.